Study of the antioxidant and anti-pancreatic cancer activities of Anchusa strigosa aqueous extracts obtained by maceration and ultrasonic extraction techniques - Chebaro, Ziad; Abdallah, Rola; Badran, Adnan; Hamade, Kamar; Hijazi, Akram; Maresca, Marc; Mesmar, Joelle Edward; Baydoun, Elias (Frontiers in Pharmacology, 2023)
Pancreatic cancer is a highly aggressive malignancy and a leading cause of cancer-related deaths worldwide. Moreover, the incidence and mortality rates for pancreatic cancer are projected to keep increasing. A major challenge in the treatment of pancreatic cancer is the lack of effective screening approaches, which contributes to its poor prognosis, indicating the need for new treatment regimens and alternative therapies, such as herbal medicine. The medicinal plant Anchusa strigosa, which is widely distributed in the Eastern Mediterranean region, is a short prickly plant from the Boraginaceae family that has been widely used in traditional medicine for treating various diseases. Nevertheless, its effect on human pancreatic cancer remains poorly investigated. In the present study, we screened the phytochemical content of A. strigosa aqueous extracts obtained by maceration and ultrasoundassisted methods (ASM and ASU, respectively) and evaluated their antioxidant effects. We also investigated their anticancer effects and possible underlying mechanisms. The results show that both extracts were rich in bioactive molecules, with slight differences in their composition. Both extracts exhibited remarkable antioxidant potential and potent radical-scavenging activity in vitro. Additionally, non-cytotoxic concentrations of both extracts attenuated cell proliferation in a time-and concentration-dependent manner, which was associated with a decrease in the proliferation marker Deleted: Study of the antioxidant and anti-pancreatic cancer 2 This is a provisional file, not the final typeset article Ki67 and an induction of the intrinsic apoptotic pathway. Furthermore, the extracts increased the aggregation of pancreatic cancer cells and reduced their migratory potential, with a concomitant downregulation of integrin β1. Finally, we showed that the ASM extract caused a significant decrease in the levels of COX-2, an enzyme that has been linked to inflammation, carcinogenesis, tumor progression, and metastasis. Taken together, our findings provide evidence that A. strigosa extracts, particularly the extract obtained using the maceration method, have a potential anticancer effect and may represent a new resource for the design of novel drugs against pancreatic cancer.